Наука та аудит. Гештальт ще не закрито - Redko О. Yu. (Statistics of Ukraine, 2023)
The article critically analyzes the state of modern Ukrainian audit science. It is noted that over the past five years there have been 310 defenses of theses in the specialty "Accounting, analysis and audit", of which only 8% were devoted exclusively to audit topics, including only 3% for obtaining the scientific degree of Doctor of Economic Sciences. Analyzing the declared topic of scientific research, the author draws attention to the fact that scientists research questions that are, so to speak, "by ear" in the professional environment. This is mainly a question of audit quality and its external and internal control. Unfortunately, there are no studies that would develop, first of all, the audit methodology, its methods and procedures, the peculiarities of auditing in computer networks. The author notes the parallel existence of audit science and practice. The reason given is the impossibility of combining scientific research with practical audit activity, the lack of interest of audit practitioners in the results of scientific research. Analyzing the scientific work of institutions of higher education, the author states the parallel existence of audit science and practice. The reason given is the impossibility of combining scientific research with practical audit activity, the lack of interest of audit practitioners in the results of scientific research. Analyzing the scientific work of institutions of higher education, the author singles out a small number of centers where audit is researched, among which examines the work of the Audit Scientific School of the National Center for Accounting and Audit of the National Academy of Statistics, Accounting and Audit. In the article, the author makes several proposals that, in his opinion, can improve the interaction of Ukrainian science and auditing practice.